Diversity and Abundance of Plants In Dry Climate in Mexican Park, Bogor Botanical Gardens - Hatipah Salamah Salamah; Siti Dela Oktavia; Savira Nuraini; Evi Muliyah (Indonesian Journal of Biology Education, 2023)
Dry climate plants are plants that can adapt in a dry environment. The Mexican Park located in the Bogor Botanical Garden has a very varied species of dry climate plants. The study aims to find out the diversity and abundance of dry-climate plants in the Mexican Park, as well as the factors that influence the dry climatic plants that can grow in the Bogor Botanical Garden. The research was carried out by direct exploration method by creating three spaces of 5m x 5m, 10mx 5m and 10m x 10m. Data analysis techniques in this study use quantitative analysis. The results of the research showed that the diversity and abundance of dry climate plants in the Mexican Park of the Bogor Botanical Garden found 15 species with a total of as many as 120 individuals. The Important Value Index (INP) of dry climate plants at all observation spots obtained a value of 2.8667%, with the highest INP being the Rhoeo discolor, so the diversity and abundance of dry-climatic plants in the Mexican Park of the Bogor Botanical Gardens can be categorized as moderate. Dry climate plants can grow in the Bogor Botanical Garden because this Mexican Park makes it very similar to its original habitat, so the nutrition and climate elements are what influence the growth factor of the plant dry climate in the Mexican Garden of Bogor.